MCDONALDISASI AGAMA PERLAWANAN KAUM SANTRI DI ERA DIGITAL - Nur, Achmad; Taufiq, Muhammad (STAI Nurul Huda Kapongan Situbondo, 2023)
People in understanding religion are more compulsive on the instant ones available in digital services. Religious rituals that prioritize the process of cleansing the mental and soul are defeated with fast food religious services without having to be a long process. Religious values and traditions are often commodities that only benefit the owners of capital. This portrait of life then becomes a challenge for religious people, especially students who often convey religion by upholding processes and traditions. Based on this reality, the question that will be answered in this study is how students fight against religious Mcdonaldization in the digital age. This type of research is qualitative research with library research design or what is often referred to as library research. This type of research is qualitative research with library research design or what is often referred to as library research. Because the data obtained is in the form of documents derived from a book and other litelature. Data collection techniques used through literature studies. Data analysis uses George Ritzer's theory or social theory approach which divides the principle of mcdonaldization into four efficiency, calculation, predictive power and control. After analysis, several findings were made, including: First, the control or domination of capital makes religious authority fade among its adherents. Second, the dominance of digital-based global traditions and cultures undermines the roots of local traditions based on processes and rituals. Third, the open resistance of the santri began to be carried out through cultural management (daurah tsaqofah), namely the management of the potential of students rooted in the natural wealth of the motherland, and the treasures of pesantren in an organized manner.